ANALISIS PENGARUH STRUKTUR MODAL, LEVERAGE DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Pan, Oktaviana; E Janrosl, Viola Syukrina (LPPM Universitas Putera Batam, 2021)
Manufacturing companies’ role is very important for country’s economy, especially for current situation where the number of investors that entered Indonesian capital market keep increasing. The most popular investment instrument among investors is investing in company shares. Before transaction, investors need to analyze and have a mature consideration because of the fluctuation of stock prices. This study aims to analyze the effect of capital structure, leverage and dividend policy on stock prices in various industrial sector of manufacturing companies listed in lndonesia Stock Exchange. Period limitation is set from 2015-2020 with population 51 companies and use purposive sampIing method. There are 6 companies that match the criteria with total 36 samples. This study apply muItiple linear regresion analysis and using SPSS 26 application. The results of the t test shows that capital structure has significant effect on stock prices, then leverage has significant effect on stock prices, while dividend policy has insignificant effect on stock prices. And for the results of F test, it shows that capital structure, leverage and dividend policy simultaneously have significant effect on stock prices.